2012
DOI: 10.1038/modpathol.2012.65
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of DLC1 gene methylation with oncogenic PIK3CA mutations in extramammary Paget's disease

Abstract: Extramammary Paget's disease is a rare cutaneous malignant neoplasm. The genetic and epigenetic mechanisms underlying its pathology remain unknown. In this study, we investigated the expression levels, and mutation and methylation status of a common tumor suppressor gene, deleted in liver cancer 1 (DLC1), and an oncogene, PIK3CA, in tumor (n ¼ 132) and normal tissues (n ¼ 20) from unrelated patients. The presence of epigenetic and genetic lesions was then correlated to the patient pathology data to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 43 publications
0
13
1
Order By: Relevance
“…37 Next-generation sequencing from this cohort is in line with previous studies. [41][42][43] In contrast to Kiniwa et al who reported mutations in ERBB2 gene, 43 we found only ERBB2 amplification but no pathogenic ERBB2 mutations in any of our cases.…”
Section: Discussioncontrasting
confidence: 99%
“…37 Next-generation sequencing from this cohort is in line with previous studies. [41][42][43] In contrast to Kiniwa et al who reported mutations in ERBB2 gene, 43 we found only ERBB2 amplification but no pathogenic ERBB2 mutations in any of our cases.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus our knowledge of the genetic features of EMPD remains limited. Previously, we reported the link between DLC1 methylation and PIK3CA mutation based on a correlation study and implicated that the genetic and epigenetic alterations may play a key role in determining the clinical and pathological features of EMPD 17. Herein, EMPD tumor samples from 144 unrelated patients were collected over a six years period for mutational analysis, and the demographic and clinical information for each of these patients was available, making this study the most comprehensive molecular analysis of EMPD to date.…”
Section: Discussionmentioning
confidence: 99%
“…This study is largely based on the series of EMPD skin lesions and matched normal skin tissues previously reported by our group 17. Updated clinical information was obtained from cancer registry files (Dermatology department of Huashan Hospital, Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we confirmed that the extensive DLC-1 methylation was associated with the KRAS mutations in CRCs but not in adenomas. Our previous study showed that DLC-1 methylation significantly correlated with PIK3CA mutations in Paget's disease [25]. These findings highlighted the interaction between genetic and epigenetic alterations in CRC, although the mechanism underlying this phenomenon requires further study.…”
Section: Discussionmentioning
confidence: 79%